Nomenclatural notes on Nadsoniella and the human opportunist black yeast genus Exophiala. Issue 6 (23rd January 2017) - Moussa, Tarek A. A.; Al‐Zahrani, Hassan S.; Kadasa, Naif M. S.; Moreno, Leandro F.; Gerrits van den Ende, A. H. G.; de Hoog, G. Sybren; Al‐Hatmi, Abdullah M. S.
Summary: The opportunistic black yeast are particularly known through the genus Exophiala, characterised by annellidic budding cells. However, this phenotype is polyphyletic within the order Chaetothyriales . Seventeen generic names are available in the family Herpotrichiellaceae, one of which is Exophiala . Future taxonomy will be based on molecular phylogeny; each multi‐species clade may qualify for one of these names. This paper focuses on the genus Nadsoniella, which is the oldest valid name in the Herpotrichiellaceae . Despite its exophiala‐like phenotype, the type species of Nadsoniella clusters in the jeanselmei‐clade, competing with the sympodial genus Rhinocladiella . In contrast, Exophiala competes with morphologically pronounced genera Thysanorea and Veronaea . Replacing the current phenotypic system for phylogenetic nomenclature requires highly stable phylogenies, which currently are not available.